Endoscopic submucosal excavation for gastric plexiform fibromyxoma: A case report and systematic review of literature - Xia, Ziqin; Zhou, Zhidai; Guo, Wei; Wang, Hongling; Wang, Fan; Zhou, Feng (Frontiers in Oncology, 2023)
Plexiform fibromyxoma (PF) is a rare mesenchymal tumor of which the pathogenesis and molecular changes are still unclear. Histologically, it is characterized by a cluster of bland spindle or ovoid cells growing in the mucoid or fibromyxoid stroma rich in small blood vessels. At present, surgical resection is the primary treatment for PF.